Embodiment touching. Il riconoscimento della corporeità nella "distante prossimità" della comunicazione aptica - Elena Falaschi (Firenze University Press, 2018)
The perspective of the embodiment is declined meaning in the primary function of touch the fundamental process of knowledge of the world. The touch, as a communication tool that allows the recognition of one's own and other people's corporeality. The nature and function of the contacts (self-contacts and hetero-contacts) and the educational value that aptic communication are analyzed in some different relational contexts (in rituals, in the symmetrical and asymmetrical relationships, depending on the gender differences, etc.). In today's postmodern society, characterized by a dominant touch culture, is needed an educational responsibility that takes the body and the "touch" as pedagogical objects, according to a methodological and epistemological approach of a critical-reflective and hermeneutic type.